Analysis of the Application of Tea Culture Experiential Courses in Teaching Chinese as a Foreign Language - Tang, Jing (INTI International University, 2020)
Tea culture is closely related to Chinese traditional culture system. In teaching Chinese as a foreign language, applying tea culture experiential courses is of great significance for improving students' Chinese communication level. This paper analyzes the advantages of this experiential courses, and researches on the teaching content and teaching methods. In order to give full play to the role of tea culture experiential courses in improving learners' language use and expanding their cultural vision.